Recent developments in evolutionary biology and their relevance for evolutionary economics - Karin Knottenbauer (Max Planck Institute of Economics, 2009)
The paper gives attention to the question of whether the development of evolutionary theories in biology over the last twenty years has any implications for evolutionary economics. Though criticisms of Darwin and the modern synthesis have always existed, most of them have not been widely accepted or have been absorbed by the mainstream. Recent findings in evolutio¬nary biology have started to question again the main principles of the modern synthesis. These findings suggest amongst others that the phenomena of co-operation, communication, and self-organization have been under¬estimated, and that selection is not the predominant factor of evolution, but only one among many. Thus, in evolutionary economics, the question is whether the popular variation-retention-selection principle is still up to date. The implications for evolutionary economics with respect to analogies, generalized Darwinism, and the continuity hypothesis are also addressed.
Keywords: 330; Analogies; evo-devo; evolutionary economics; evolutionary biology; co-operation; genes; Lamarckism; modern synthesis; neo-Darwinism; selection; self-organization